(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the functional and radiological outcomes of Ilizarov fixator in managing open fractures shaft of femur. Methods: This descriptive study was conducted in Orthopaedic department Aga khan University hospital Karachi from 23rd January 20015 to 25th December 2020.All adults patients of both gender and age with open fracture femur fulfilling the inclusion criteria were operated with Ilizarov fixator. Functional and radiological outcomes were determined by using the Association for the Study and Application of Methods of Ilizarov (ASAMI) scoring system. The bone results and functional results were graded as excellent, good, fair and poor as per ASAMI scoring system. Results: We operated 32 patients of open fractures femur with Ilizarov fixator. The mean age was 41±7 years. Male patients were 31(96.87%) and female 1(3.12%). Right sided femur shaft fracture was present in 17(53.12% ) and left sided in 15(46.87%). The aetiology of fractures was road traffic in 24( 75%) and gunshot in 8( 25%) patients. Gustilo Anderson type IIIA fractures were present in 22(68.75%) and type IIIB in 10(31.25%) patients. Post operative bone results using ASAMI score were excellent in 16(50%), good in 15(46.87%) and fair in 1(3.12% ) patient. Function result using ASAMI score were excellent in 18(56.25%),good in 13(40.62%) and fair in 1(3.12%) patient. The average cost of treatment was 350,000 rupees. Conclusion: Illizarov fixator is a cost effective option for managing acute open femur fractures. Excellent and good functional and radiological results were achieved in majority of our patients.